PERBANDINGAN FUNGSI KOGNITIF ANTARA SISWA KATEGORI BERAT BADAN NORMAL DAN OBESITAS: Studi Deskriptif pada siswa SMAN 3 Subang - Febby Zelphira, - (2019)
The purpose of this research was to determine the relationship of cognitive function between students in normal weight categories and obesity in high school. The method used in this research is descriptive quantitative research.The population in this study were high school students in Subang City. The technique in this study uses Saturation Sampling and Simple Random Sampling techniques. The samples that have been determined in this study are 44 students high school using descriptive research designs. The instruments used in this study is Growth Chart, grid concentration exercise, digit span, and TPA (Academic Potential Test). The results of the analysis, the value of Thitung for data with Equal Variances Assumed is 2.409 with value of probability (p-value) is 0.020. Based on the data from the analysis, the value of Thitung (2.049) with a probability value (0.020) is smaller (<) than 0.025. Then H0 is rejected, so it can be concluded that there are significant differences in cognitive functions between normal weight categories and obesity.